Hydroponic kale planting training for people affected by Covid-19 - Astuti, Cindy Cahyaning; Nurmalasari, Intan Rohma; Hasanah, Fitria Nur (Community Empowerment, 2021)
Various economic problems occurred due to the Covid-19 pandemic, including a decrease in income due to layoffs for factory employees and a decrease in sales turnover for traders. This is generally experienced by the people of Pilang Village. In this community service activity, the solution offered is to carry out food self-sufficiency at the family level by planting hydroponic kale. Hydroponic kale planting can be done by utilizing the vacant land around the house. Hydroponic farming technology can be an option to support food security, especially in the family environment. Hydroponic vegetable planting can be developed into a family vegetable garden, even if properly cared for can be a family economic empowerment. Hydroponic Kale planting training activities provide an increased understanding of the procedures for planting kale with hydroponic technology. The increase in participants' understanding was measured using a questionnaire. In all aspects of understanding the cultivation of kale with hydroponic technology has increased. So, the training can increase the understanding of PKK cadres in Pilang Village in planting hydroponic kale.